Chorda tympani nerve modulates the rat’s avoidance of calcium chloride - Golden, Glen J. (2011)
Calcium intake depends on orosensory factors, implying the presence of a mechanism for calcium detection in the mouth. To better understand how information about oral calcium is conveyed to the brain, we examined the effects of chorda tympani nerve transection on calcium chloride (CaCl(2)) taste preferences and thresholds in male Wistar rats. The rats were given bilateral transections of the chorda tympani nerve (CTX) or control surgery. After recovery, they received 48-h two-bottle tests with an ascending concentration series of CaCl(2). Whereas control rats avoided CaCl(2) at concentrations of 0.1 mM and higher, rats with CTX were indifferent to CaCl(2) concentrations up to 10 mM. Rats with CTX had significantly higher preference scores for 0.316 and 3.16 mM CaCl(2) than did control rats. The results imply that the chorda tympani nerve is required for the normal avoidance of CaCl(2) solution.